Effects of L-carnitine and L-acetyl-carnitine on testicular sperm motility and chromatin quality - Elham Aliabadi; Malek Soleimani Mehranjani; Zahra Borzoei; Tahereh Talaei-Khozani; Hossein Mirkhani; Hamed Tabesh (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2012)
Background: Sperm cells extracted from testes (TESE) have poor chromatin quality and motility. Various substances are used in the laboratory to increase sperm motility and improve the ART outcomes; however, there are few research which considered improving both sperm motility and chromatin quality. Objective: The aim of this investigation was to evaluate the improvement of the testicular sperm motility and chromatin quality exposed to L-carnitine (LC) and L-acetyl-carnitine (LAC), which are normally concentrated in testis and epididymis, compared with Pentoxifylline (PF), which used for sperm motility enhancement in IVF procedures. Materials and Methods: TESE samples from 30 male mice divided into four parts. The sperm samples were added to Ham' F10 (control) or the media contained 1.76mM of LC, LAC or PF), then, the samples were kept in the room temperature for 30, 90 and 180 min. At each time step, sperm motility and chromatin quality were assessed. Chromatin quality was evaluated by chromomycin A3 and aniline blue. Statistical analysis was performed using one way analysis of variance (ANOVA). A p-value less than 0.05 were accepted as a statistically significant difference. Results: The results showed LC, LAC and PF significantly increased the sperm motility. However, sperm chromatin quality only improved significantly by administration of LC and LAC. Conclusion: Administration of LC and LAC to the testicular sperm samples can lead to improve both sperm motility and chromatin quality. It may be because they can mimic in vivo sperm condition during late spermatogenesis.